Impact of Treatment Modality on Vascular Function in Coarctation of the Aorta: The LOVE‐COARCT Study. Issue 7 (2nd April 2019) - Martins, José D.; Zachariah, Justin; Selamet Tierney, Elif Seda; Truong, Uyen; Morris, Shaine A.; Kutty, Shelby; de Ferranti, Sarah D.; Guarino, Maria; Thomas, Boban; Oliveira, Diana; Marinho, António; António, Marta; et al.
Abstract : Background: Optimally treated patients with coarctation of the aorta remain at risk for late vascular dysfunction. The effect of treatment modality on vascular function is unknown. The LOVE‐COARCT (Long‐term Outcomes and Vascular Evaluation After Successful Coarctation of the Aorta Treatment) study was done to compare vascular function in patients with coarctation of the aorta treated with surgery, balloon dilation (BD), or stent implantation. Methods and Results: In treated coarctation of the aorta patients without residual coarctation, we prospectively compared aortic stiffness by applanation tonometry and cardiac magnetic resonance; endothelial function by endothelial pulse amplitude testing; blood pressure (BP) phenotype by office BP, ambulatory BP monitoring, and BP response to exercise; left ventricular mass by cardiac magnetic resonance; and blood biomarkers of endothelial function, inflammation, vascular wall function, and extracellular matrix. Participants included 75 patients treated with surgery (n=28), BD (n=23), or stent (n=24). Groups had similar age at enrollment, coarctation of the aorta severity, residual gradient, and metabolic profile, but differed by age at treatment. Prevalence of systemic hypertension, aortic stiffness, endothelial function, and left ventricular mass were similar among treatment groups. However, BD patients had more‐distensible ascending aortas, lower peak systolic BP during exercise, less impairment in diurnal BP variation, and lower inflammatory biomarkers. Results were unchanged after adjustment for potential confounders, including age at treatment. Conclusions: In our cohort of patients without residual coarctation, treatment modality was not associated with major vascular outcomes, even though there were some favorable vascular characteristics in the BD patients. Although this suggests that choice of treatment modality should continue to be driven by likelihood of achieving a good anatomical result, more long‐term studies are required to assess the clinical significance of the more‐optimal results of secondary markers of vascular function in BD patients. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03262753. Abstract : See Editorial Hametner et al